Tren-Tren Wacana Studi Al-Qur’an dalam Pandangan Orientalis di Barat - Muhammad Anshori (Nun : Jurnal Studi Alquran dan Tafsir di Nusantara, 2018)
This paper discusses about the history or trend of the Qur’anic studies in the West in general which is still developing until now. There are three focuses of discussion in this paper, namely the history of the translation of the Qur›an, Jewish-Christian Influences on the Qur›an, and a critical study of the Qur›an. Before discussing this matter, this paper also discusses a little about Mushaf ‘Usmānī or what is now called the Qur›an. The beginning of the study of the Qur›an in the West began with translation and later developed into a critical study of the Qur›an itself. The first translation of the Qur’an was carried out by Peter the Venerable and Abbot of Cluny in Latin. This translation was later refined by Robert of Ketton in 1143. After being translated, it was only published for the first time in 1543 AD. After the translation of this translation, it was later followed by other translations in various languages. The study of the Qur’an began to draw attention in the West when Theodor Nӧldeke wrote a book on the history of the Qur’an (Geschichte des Qorāns/Tārīkh al-Qur’ān, The History of The Qur›an). Some Western scholars said that the Qur›an has been influenced by the Judeo-Christian tradition and thus has some similarities. Some Western scholars also conduct critical studies of the Qur’an, some even want to make another version of the Qur’an. The views of Western scholars who are «eccentric» have been denied by Muslim scholars themselves. It can be said that this paper discusses the Orientalist views of the Qur›an.